Pengaruh Strategi Pemasaran Online Terhadap Keputusan Pembelian Konsumen Pada Produk Mixue di Kota Jayapura (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
This research discusses the influence of online marketing strategies on consumer purchasing decisions for Mixue products in Jayapura City. This research uses qualitative methods to understand social phenomena and people's perspectives on these topics. Mixue is a franchise company that sells soft ice cream and tea drinks, originating from China and has expanded to Indonesia. Mixue's marketing strategy includes low prices, targeting lower market segments, and social marketing via social media. Mixue has also expanded to Papua by opening several branches there. The conclusions of this research are written carefully, fairly and honestly, based on the facts of existing research findings, and being careful if there are attempts at generalization. The sources used cover various topics related to marketing management, integrated marketing communications, consumer behavior, and product innovation. This research provides insight into how online marketing strategies can influence consumer purchasing decisions, especially Mixue products in Jayapura City.